BPM-SCRUM Integrated Model with Digital Marketing to Increase Patient Recruitment Rate in Mental Health Services - Fhon Palacios, Mariana (2022)
In a pre-pandemic scenario, 350 million people in the world suffer from depression, 60% of whom do not receive treatment. In Peru, every 22 minutes someone tries to take his or her own life. In the world, 800 000 people do so, mainly due to depression. Of the people who suffer from this disease, 75% do not do anything about it. This is due to the barrier of misinformation about mental health, its importance and the services available. In spite of this, in the case of the people who do get treatment, many of them end up abandoning it because it does not meet the special expectations of each patient. Therefore, a redesign of the patient attraction process has been proposed using BPM and Scrum Methodology. This proposal will also apply Digital Marketing to launch a web platform that automates the entire patient recruitment process. The current patient acquisition rate is 50% of the industry standard and the rate of digital tools usage is 60%. After the implementation of the proposed model, these rates increased to 76% and 100%, respectively.